Bibliometric Analysis of Teacher Self-Efficacy in Primary Education - Aulia Wulandari; Sukarno Sukarno; Matsuri Matsuri (AL-ISHLAH: Jurnal Pendidikan, 2023)
Teacher self-efficacy is the ability to believe in controlling or mastering certain situations. The level of self-efficacy of elementary school teachers will affect their work. This study aims to uncover study trends related to primary school teacher self-efficacy over the last three decades by using bibliometric analysis. The Scopus database was used to collect articles that matched the criteria, eventually yielding 164 articles from 1994–2022. The results showed that "self-efficacy" was the most widely used keyword in article publications, while the researchers focused on teacher self-efficacy in elementary schools. Turkey, Australia, and China are the countries that produce the most publications in this field. The journals that produce the most publications are the International Journal of Inclusion and Egitim ve Bilim. Betoret f.d, Palmer d, and De Veve d are the authors with the highest number of citations. Based on the results of this analysis, it shows that "self-efficacy, teacher self-efficacy, and inclusive education" are the most recently used keywords in the article. The results of this study indicate that in addition to well-known countries that discuss teacher self-efficacy in primary school education, this study also needs to be carried out in other developing countries. It is suggested that developing countries can develop research in this area and that teacher self-efficacy should be more focused on teacher self-development and teacher confidence when teaching.